A REVISTA CAROS AMIGOS E SEU MODO DE NARRAR HISTÓRIAS - Chagas, Luciana Almeida das (2009)
The journalistic field creates norms that legitimate a unique mode of making journalism: the hegemonic journalism made by the mass media. Based on an analysis of narratives used in reports published in the Caros Amigos magazine, this dissertation makes it evident that a magazine's mode of making journalism does not necessarily follow what is authorized by the journalistic field, and thus it may cause an overflow. This research encompasses the history of the Caros Amigos magazine and it specially points out its mode of production, its journalists profiles and its narrative structure of reports. In this work it is understood that the mode of making journalism in the Caros Amigos magazine may also contribute to the reflection and the review of journalism as practiced in our society today